Massage Therapy for Dystonia: a Case Report - Lipnicki, BSc, RMT, Michelle (International Journal of Therapeutic Massage & Bodywork, 2020)
Background: Dystonia is a neurological disorder, characterized by involuntary muscle spasms and tremors, resulting in abnormal movements and posture. Symptoms include pain, spasms, tremors, and dyskinesia—a difficulty in performing voluntary muscular movements. Conventional treatments include medication, botulism injections, and surgical intervention. Many dystonia patients seek complementary and alternative medicine (CAM) therapies, such as massage, but these treatments are not well documented. This clinical case study documents massage treatment for dystonia for a specific individual. Purpose: To examine the effects of massage therapy on pain, spasms, and dyskinesia in activities of daily living (ADL), in a patient diagnosed with dystonia as an adult, following trauma. Methods: A student massage therapist administered 5 massage treatments over a six-week period to a 51-year-old female patient diagnosed with dystonia. The patient presented with symptoms of pain, spasms, tremors, and dyskinesia in ADL. Techniques applied included Swedish massage and hydrotherapy to decrease pain and spasms, and myofascial release and stretching, to decrease dyskinesia. Treatments aimed to increase overall relaxation. Remedial exercise was given to practice smoother movement patterns. Pre- and postnumeric rating scales (NRS) for pain were evaluated each session. Frequency of night pain and spasms, the Modified Bradykinesia Rating Scale (MBRS), the Timed Up and Go (TUG) test, the Functional Rating Index (FRI) and the Modified Gait Efficacy Scale (MGES) were measured at the start and end of the study. Results: Posttreatment pain intensity generally remained the same or decreased. Positive outcomes were exhibited in the frequency of night pain and spasms, TUG, MBRS, and FRI test scores. The MGES score was negatively affected. Conclusion: The results suggest massage therapy may temporarily decrease pain intensity, pain and spasm frequency, and dyskinesia in ADL, associated with dystonia.